Characterization of CTX-M-14-producing Escherichia coli from food-producing animals - Liao, Xiao-Ping; Xia, Jing; Yang, Lei; Li, Liang; Sun, Jian; Liu, Ya-Hong; Jiang, Hong-Xia (Frontiers in Microbiology, 2015)
Bacterial resistance to the third-generation cephalosporin antibiotics has become a major concern for public health. This study was aimed to determine the characteristics and distribution of blaCTX-M-14, which encodes an extended-spectrum β-lactamase, in E. coli isolated from Guangdong Province, China. A total of 979 E. coli isolates isolated from healthy or diseased food-producing animals including swine and avian were examined for blaCTX-M-14 and then the blaCTX-M-14 –positive isolates were detected by other resistance determinants (ESBLs, PMQR, rmtB and floR) and analyzed by phylogenetic grouping analysis, PCR-based plasmid replicon typing, multilocus sequence typing and plasmid analysis. The genetic environments of blaCTX-M-14 were also determined by PCR. The results showed that fourteen CTX-M-14-producing E. coli were identified, belonging to groups A (7/14), B1 (4/14) and D (3/14). The most predominant resistance gene was blaTEM (n= 8), followed by floR (n=7), oqxA (n=3), aac(6’)-1b-cr (n=2) and rmtB (n=1). Plasmids carrying blaCTX-M-14 were classified to IncK, IncHI2, IncHI1, IncN, IncFIB, IncF or IncI1, ranged from about 30kb to 200kb, and with insertion sequence of ISEcp1, IS26 or ORF513 located upstream and IS903 downstream of blaCTX-M-14. The result of MLST showed that 14 isolates had 11 STs, and the 11 STs belonged to 5 groups. Many of the identified STs are reported to be common in E. coli isolates associated with extraintestinal infections in humans, suggesting possible transmission of blaCTX-M-14 between animals and humans. The difference in the flanking sequences of blaCTX-M-14 between the 2009 isolates and the early ones suggests that the resistance gene context continues to evolve in E. coli of food producing animals.